Reinterpretasi Batasan Aurat Wanita dalam Pandangan M. Quraish Shihab dan Wahbah az-Zuhaili: Studi Komparatif - Kharismafitri M.Y. Marengke; Ahmad Nurrohim (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The topic of Muslim women’s attire is always an intriguing subject of study, particularly within the discourse of contemporary Islam, where its relevance remains a subject of ongoing debate. Differences in methodology and contextual perspectives often fuel these debates across various circles, including discussions regarding the transformation of the definition of “aurat” from classical fiqh to a contextual approach. This paper aims to examine the similarities and differences in the interpretations of M. Quraish Shihab and Wahbah az-Zuhaili in their works, Tafsir al-Misbah and Tafsir al-Munir, as well as al-Fiqh al-Islami wa Adillatuhu, regarding the boundaries of women’s aurat. This paper is based on qualitative research using a literature review (library research) methodology. The research data was analyzed using the comparative exegesis (tafsir muqaran) method through the steps of data display, identifying characteristics, and critical evaluation. The research focuses on two main verses: Surah al-Ahzab [33]:59 and Surah an-Nur [24]:31. The results of this study indicate that M. Quraish Shihab and Wahbah az-Zuhaili share the view that the face and palms are not considered aurat in principle. However, they differ in their methodologies and the nature of the legal ruling regarding the hijab; Shihab places greater emphasis on cultural standards of modesty ('urf), while Az-Zuhaili adheres to classical legal standards that are fixed in nature as a form of worship and moral protection.